Increasing Permeability of Coal Seam and Improving Gas Drainage Using a Liquid Carbon Dioxide Phase Transition Explosive Technology. (27th August 2018) - He, Wenrui; He, Fulian; Zhang, Kun; Zhao, Yongqiang; Zhu, Hengzhong
Abstract : The low permeability of coal seams makes gas drainage difficult in lots of coal mines. This study presents a low-temperature, safe, and efficient liquid carbon dioxide phase transition explosive technology (LCDPTET) to increase the permeability of coal, thereby improving the efficiency of gas drainage and eliminating the dangers of coal and gas outburst. Meanwhile, an integrated approach for experimental determination, numerical simulation, and field testing was applied to study the damage ranges of coal and to determine a reasonable spacing between the gas drainage hole and blast hole. A numerical simulation model of liquid carbon dioxide phase transition explosion (LCDPTE) was built, and the damage index M was introduced to analyze the degree and range of coal damage after explosion at different spacings between the blast hole and the gas drainage hole. Furthermore, another aim was the assessment of the permeability changes and comparison of the gas drainage effects of different borehole spacings. The results showed that as the borehole spacing became smaller, the degree of coal damage around the gas drainage hole increased, and the gas drainage effect improved. However, to avoid the collapse of the gas drainage hole, the gas drainage holes should not be located in the crushing zone caused by LCDPTE. Based on the numerical analysis conducted to guide the borehole arrangement of the field test, the latter was carried out to study the increasing ranges of permeability of coal and the drainage effect after explosion. The results indicated that LCDPTET could greatly improve the permeability of the coal seam and gas drainage efficiency. In addition, this new technology could not only improve the safety and efficiency of mine production but could also turn carbon dioxide into an effective energy source worthy of popularization and application.